2015
DOI: 10.5152/tud.2015.54521
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between histopathology and age factor in patients who were operated for renal masses

Abstract: Objective: Renal neoplasms have a predilection to occur in older patients and they are often malignant. They may have different structural characteristics according to age groups. In our study, we have investigated age-related demographic characteristics of the patients who were operated because of suspected malignant renal masses. Material and methods:Between 2010 and 2014, 129 patients were treated surgically for suspected malignant renal masses at our institution. These cases had undergone open radical, ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…Similarly, Eggener et al, (2004) reported benign pathology in 36% of young females and 9.5% in males. It is suggested that nephron sparing surgery should be preferred to young women because of these high benign mass rate (Yıkılmaz et al, 2015;Eggener et al, 2004). In our study, benign pathologies were detected in 35% of the young women and in 13,6% of the young males and this difference was statistically significant (p<0,05).…”
Section: Resultssupporting
confidence: 47%
See 2 more Smart Citations
“…Similarly, Eggener et al, (2004) reported benign pathology in 36% of young females and 9.5% in males. It is suggested that nephron sparing surgery should be preferred to young women because of these high benign mass rate (Yıkılmaz et al, 2015;Eggener et al, 2004). In our study, benign pathologies were detected in 35% of the young women and in 13,6% of the young males and this difference was statistically significant (p<0,05).…”
Section: Resultssupporting
confidence: 47%
“…Studies in relation to gender and histopathology have reported that benign pathologies are seen at high rates in young females. Yıkılmaz et al, (2015) reported that 40% of young females had benign pathologies, while in males this rate was reported as 4% (p <0.05). Similarly, Eggener et al, (2004) reported benign pathology in 36% of young females and 9.5% in males.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…2 In a study from Turkey, Yıkılmaz et al divided the patients into two groups according to age as follows ≤50 years and >50 years. 16 They reported that there was no significant difference regarding to gender, tumor size, laterality, surgical and pathologic features between two groups. 16 The TNM stage is a broadly utilized prognostic factor for cancer survival.…”
Section: Discussionmentioning
confidence: 95%
“…16 They reported that there was no significant difference regarding to gender, tumor size, laterality, surgical and pathologic features between two groups. 16 The TNM stage is a broadly utilized prognostic factor for cancer survival. 17 Şimşek et al reported that radiological lymph node involvement and stage were independent predictors that affecting the survival rates of renal cell carsinoma patients.…”
Section: Discussionmentioning
confidence: 95%